Modern Analytical Techniques for Drug Delivery Systems Characterization - Rus, Iulia; Tertis, Mihaela; Cristea, Cecilia; Sandulescu, Robert (Current Analytical Chemistry, 2021)
Recently, different strategies such as personalized therapy, dose adjustment, therapy monitoring and targeted drug delivery (disease-specific localization), were adopted for improving efficacy ratio of medicines that are currently in use. From a therapeutical point of view, to reach the optimal concentrations in the target organ or tissue, it is necessary to increase the administered dose, which is accompanied by an increase in the frequency and intensity of the side effects, many of them undesirable and distressing for the patient. Therefore, designing targeted delivery systems for a specific organ or tissue is the ideal solution, ensuring the necessary concentrations at the site of action and avoiding or at least significantly reducing the side effects. An overview of the modern analytical techniques currently used for the drug delivery systems characterization was intended in this review with a focus on those commonly used.
Keywords: dose adjustment